Patterns Of Arabic Poetic Vision In The Collection Of Al-Abbas Bin Mardas Al-Sulami/ أنماط الرؤيا الشعرية في ديوان العباس بن مرداس السلمي - Ghadeeb, Mahmood Ahmed Shakir (Ijaz Arabi Journal of Arabic Learning, 2024)
The poetry of Al-Abbas bin Mardas Al-Sulami, a unique voice from the pre-Islamic and early Islamic eras, presents a distinct poetic vision. This research delves into his poetic text, employing a method that involves presenting his poetry, elucidating the features of his poetic vision, and exploring the external factors that shaped his thoughts. The findings of this study reveal that Al-Abbas Ibn Mardas challenged some of the prevailing Arab values, offering a unique perspective before the advent of Islam. Abbas bin Mardas, a poet of his time, was not just a passive observer but an active participant in shaping the artistic landscape. He rejected social injustices, which he believed were breeding grounds for hatred, and sought to revolutionize the ancient Arabic poem with his direct influence from Islam. His focus in the Islamic era was on supporting the Prophet. This research also highlights his influence on other poets of the era, such as Hassan bin Thabit, Kaab bin Malik Al-Ansari, and Kaab bin Zuhair, underscoring his significant role in the development of Arab thought after the arrival of Islam.